Reescrituras del negativo: Variaciones en las modernas teodiceas, entre Leibniz y Rosmini - Peratoner, Alberto (Cauriensia, 2023)
The present contribution aims to investigate the variations occurred in the theoretical elaboration of theodicy - conceived in the classical sense as the treatment of the problem of evil in the face of the goodness and justice of God - in modern philosophy, from Leibniz to Rosmini. For the comprehension of Leibnizian theodicy result the fundamental importance of the modern evolution of the ontology of possibility, in relation to actual being. The theoretical framework is ingeniously reconsidered by Rosmini on the background of his metaphysics of the three categorial forms of being, thanks to which the roveretan philosopher can confer a greater solidity to the outlined perspectives, overcoming some critical aspects of the Leibnizian conception.